Voice Reconstruction: Integration and Value Chain Upgrading of Radio Advertising in the New Media Context - Qi, Shuangshuang (International Journal of Social Sciences and Public Administration, 2025)
With the rapid evolution of digital communication and the diversification of media ecosystems, traditional radio advertising is undergoing a profound transformation. The rise of mobile internet, smart devices, and personalized media has fragmented audiences and challenged radio’s long-standing dominance. At the same time, new audio platforms-such as podcasts, online radio, smart speakers, and in-car media-have redefined the cultural and commercial value of sound. Audio advertising is shifting from a single “voice dissemination” model to a more complex process of “voice reconstruction,” involving innovation across content, technology, and business models. This paper explores how radio advertising achieves integration and value chain upgrading in the new media environment. Through literature synthesis, theoretical reasoning, and representative case studies, it proposes a “media convergence–value chain upgrading” model that explains how intelligent technologies, immersive storytelling, and cross-platform collaboration transform radio advertising into an intelligent, interactive, and multi-scenario ecosystem.